Ten Years of Research on Spiritual Leadership: a Bibliometric Analysis - Adli, Adli; Permana, Johar; Prihatin, Eka; Aedi, Nur (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This bibliometric analysis explores the research landscape on spiritual leadership from 2014 to 2024, utilizing Scopus data to evaluate publication trends, key contributors, keyword co-occurrence, and directions for future research. A total of 268 peer-reviewed journal articles were analyzed through bibliometric methods. The findings reveal significant growth in research, particularly after 2018, with annual increases observed thereafter. In terms of contributions, Indonesia, China, and the United States stand out, with Indonesia leading in publication volume, while the United States and Thailand exhibit higher average citation impacts, indicating varying levels of influence across regions. Thematic analysis highlights a strong focus on workplace spirituality, employee well-being, job satisfaction, and organizational commitment. Network visualization emphasizes the central role of spiritual leadership and its associations with ethical leadership, employee performance, and organizational citizenship behavior. Emerging themes include sustainability, innovation, and crisis leadership, particularly in response to the COVID-19 pandemic. These findings suggest promising research opportunities in crisis management, sustainability, and cross-cultural applications of spiritual leadership, underscoring the field’s dynamic and expanding relevance in addressing contemporary organizational challenges.